Restitution of State Financial Losses Under the Anti-Corruption Law: A Progressive Legal Reconstruction Approach - Mohamad Qosim Thalib; Fence M. Wantu; Dian Ekawaty Ismail (International Journal of Law, Crime and Justice, 2025)
This research examines the reconstruction of Article 4 of the Corruption Crime Law regarding the return of state financial losses through a progressive legal approach. This research uses sociological normative legal research methods with statutory and conceptual approaches. The results show that the provision of Article 4 which states that the return of state financial losses does not eliminate punishment needs to be recon-structed to accommodate the principles of restorative justice and legal incentives for perpetrators who voluntarily return state losses. The reconstruction does not completely eliminate punishment, but provides different treatment based on the level of cooperation of the perpetrator. For corruption cases with relatively small state losses, a restorative justice approach is more appropriate considering that case handling costs are often greater than the value of losses. This research recommends reformulating Article 4 to provide op-portunities for administrative settlement within a certain timeframe before proceeding to criminal pro-ceedings.